Assessment of Charge Transport through Barrier Membranes before Application on Materials Surfaces - Nardeli, Jéssica Verger [UNESP]; Fugivara, Cecílio Sadao [UNESP]; Benedetti, Assis Vicente [UNESP] (FapUNIFESP (SciELO), 2022)
This work aims at investigating the charge transfer resistance (RCT) of the two membranes derived from vegetable oils which are intended to protect materials against corrosion. The membranes were characterized by thickness measurement (328±1 μm and 491± 1 μm), atomic force microscopy (AFM) to estimate of roughness (<0.5 μm), Raman spectroscopy while the RCT values were evaluated by electrochemical impedance spectroscopy (EIS) in 0.1 mol/L KCl solution. EIS was used to measure the impedance at low frequency (Z0.01Hz ≅ 109 Ω cm2), RCT ≅ 109 Ω cm2 and exchange current density (i0 ≅ 10-11 Ω cm2), employing simple instrumentation. The thickness of the membrane must be considered for coherent interpretation of the impedance results. The study of electrolytes permeation in membranes is important to previously estimate the lifetime offered to a substrate over the time of immersion even before being applied to the metallic surface. The impedance measurements demonstrated that the most resistant membrane to permeation presented a RCT around 2 GΩ cm2. This EIS measurements approach enables the optimization of membrane fabrication by conveniently identifying the best formulation.
Keywords: corrosion protection; Membrane; permeation; pristine organic film